Análisis de la eficiencia de los software utilizados en la industria colombiana para modelar piezas en 3d que puedan ser utilizadas en la manufactura de moldes de inyección - Quintero Dallos, Robinson (Universidad Antonio Nariño, 2022)
This project seeks the appropriate route for the elaboration of organic modeling, in the software most used by Industrial Designers in Colombia, it also defines the export formats that can be used in CAM software for the creation of plastic injection molds, later the process is exposed the information acquired to students of Industrial Design, the methodology used is focused on learning, and teaching software in this case of 3D modeling.